POLITICAL CULTURE AND SOCIETY'S POLITICAL ORIENTATION IN THE DIGITAL AGE - Budiana , Muhammad (Sean Institute, 2023)
This study aims to analyze the relationship between political culture and people's political orientation in the digital era. The digital era has had a significant influence on the way people obtain information and engage in political activities. In this context, political culture is important because it can affect the political orientation of society. This study uses a qualitative approach with qualitative descriptive analysis techniques. The results of the study show that political culture which consists of political values, political participation, and political mindset influences people's political orientation in the digital era. Societies that have a participatory political culture and democratic values tend to have a more active and critical political orientation in the digital era. Meanwhile, people who have an authoritarian political culture and traditional values tend to have a more passive and conservative political orientation in the digital era. This research contributes to the understanding of the relationship between political culture and people's political orientation in the digital era and provides implications for the development of strategies for political participation and management of social media in the future.